Microsoft Repository Version 2 and The Open Information Model - Bernstein, Phil; Bergstraesser, Thomas; Carlson, Jason; Pal, Shankar; Sanders, Paul; Shutt, David (Information Systems, 1999)
Microsoft Repository is an object-oriented meta-data management facility that ships in Microsoft Visual Studio and Microsoft SQL Server. It includes two main components: A repository engine that implements a set of object-oriented interfaces on top of a SQL database system. A developer can use these interfaces to define information models (i.e., schemas) and manipulate instances of the models. The Open Information Model, which is a set of information models that cover object modeling, database modeling, and component reuse. The repository system is designed to meet the persistent storage needs of software tools. Its main technical goals are: Compatibility with Microsoft’s Component Object Model (COM) architecture Extensibility by customers and independent software vendors, so they can add behavior to objects stored by the repository engine and extend information models provided by Microsoft and others. Flexible and efficient versioning, configuration management, and checkout/checkin to support team-oriented activities. This paper describes the programming interface and implementation of the repository engine and the Open Information Model.